Syndromes calculation at multiple errors decoding by Lagrange codes - Кубицкий, В. И. (Problems of Informatization and Control, 2009)
Procedures of syndromes values calculation at decoding of multiple errors by Lagrange codes are resulted. The amounts of operations in the eventual fields and memory space for storage of constants during realization of the procedures are defined. The comparative estimation of the considered procedures is given